Imperialism from the Perspectives of Two British Authors, George Orwell and Rudyard Kipling - Saputri, Liliani (Universitas Sebelas Maret, 2021)
George Orwell and Rudyard Kipling are British authors who are different in viewing imperialism. The essays “Shooting an Elephant” and “A Hanging” by George Orwell and a novel “The Jungle Book” by Rudyard Kipling, represent imperialism as the main point. This research finds out the intention of George Orwell and Rudyard Kipling for describing the concept of imperialism. It also purposes to find out the way the authors express their thoughts in literary work as the response towards imperialism. This research applies sociology of literature approach in analyzing data and employs Alan Swingewood’s theory in digging how George Orwell and Rudyard Kipling develop their thoughts about imperialism into work. This research reveals that George Orwell and Rudyard Kipling’s works are expression of their idea that concerns not on the difference in the type of works, but on the values in each work to treat other people as human being. Through his works, Orwell shows people to do not violating others’ right. Meanwhile, Kipling introduces to children for imparting imperialism since childhood. These contradicting way describing imperialism encourage both of the authors to show their intention in supporting anti-imperialism and pro-imperialism concept.